2016
DOI: 10.1080/07391102.2015.1128979
|View full text |Cite
|
Sign up to set email alerts
|

An anti-DNA antibody prefers damaged dsDNA over native

Abstract: DNA-protein interactions, including DNA-antibody complexes, have both fundamental and practical significance. In particular, antibodies against double-stranded DNA play an important role in the pathogenesis of autoimmune diseases. Elucidation of structural mechanisms of an antigen recognition and interaction of anti-DNA antibodies provides a basis for understanding the role of DNA-containing immune complexes in human pathologies and for new treatments. Here we used Molecular Dynamic simulations of bimolecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Anti-dsDNA antibodies can bind to a complex of native dsDNA or modified DNA that contains a thymine dimer (generated during DNA photodamage). The chemically modified dsDNA may acquire a higher affinity for autoantibodies and form more stable complexes (29). Otherwise, antibodies can react with many non-DNA antigens in target cells and tissues: annexin II, α-actinin, laminin, collagen III, collagen IV, entactin, complement receptor type 1 (C1q), N-methyl-d-aspartate receptor (NMDAR), ribosomal P proteins, heparan sulfate, and others (3039) (Table 1).…”
Section: The Origin Of Anti-dsdna Antibodiesmentioning
confidence: 99%
“…Anti-dsDNA antibodies can bind to a complex of native dsDNA or modified DNA that contains a thymine dimer (generated during DNA photodamage). The chemically modified dsDNA may acquire a higher affinity for autoantibodies and form more stable complexes (29). Otherwise, antibodies can react with many non-DNA antigens in target cells and tissues: annexin II, α-actinin, laminin, collagen III, collagen IV, entactin, complement receptor type 1 (C1q), N-methyl-d-aspartate receptor (NMDAR), ribosomal P proteins, heparan sulfate, and others (3039) (Table 1).…”
Section: The Origin Of Anti-dsdna Antibodiesmentioning
confidence: 99%
“…In addition, authors have also reported that anti-dsDNA can bind to many cell types in the renal tissues—including cultured mesangial cells, podocytes, vascular endothelial cells, and proximal tubular epithelial cells—to induce cell proliferation, apoptosis, and enhanced gene/protein expression for inflammation/fibrosis [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. It is equally interesting that anti-dsDNA antibodies can recognize diverse DNA structures, such as single-stranded DNA, Z-form DNA, bent or elongated dsDNA, DNA-RNA hybrids, peptide-nucleic acid hybrids, and locked-nucleic acids (LNA) [ 88 , 89 , 90 ]. Accordingly, anti-dsDNA antibodies can bind to a complex of native dsDNA or modified DNA containing the thymine dimer.…”
Section: Recent Advances In the Pathophysiologic Mechanisms For Lnmentioning
confidence: 99%
“…Thus, in addition to anti-DNA autoantibodies being crucial for the diagnosis of SLE they are promising targets for therapy 4 . However, in spite of growing knowledge on anti-DNAs, there is still a lack of methods for their specific detection 5 .…”
Section: Introductionmentioning
confidence: 99%